Challenges in Developing Sequence Diagrams (UML) - Kurniawan, Tri Astoto; LÃª, Lam-Son; Priyambadha, Bayu (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
During the object-oriented software design phase, the designers have to describe the dynamic aspect of the system under development through the most common interaction diagram variant in UML 2.0, i.e. sequence diagrams. Some novice designers, including undergraduate and postgraduate students, suffer from making inappropriate models due to insufficiently detailed guidance required to develop such sequence diagrams. This paper classifies some potential mistakes which are likely performed by such novice designers, and discusses the corresponding corrections. We summarized such mistakes based on our long experiences in teaching software modeling classes as well as software analysis and design classes. There were classified twenty-one potential mistakes with respect to the syntactical and semantical correctness of the developed models. It is concluded that novice designers have to be aware and take into account the identified mistakes in such a way they can produce correct sequence diagrams.